Searching for the Roots of Contemporary Branding: Study of Cylinder Seals from the Dawn of Ancient Egypt (UNWE Yearbook, 2023)
The paper presents a small part of the outcome of scientific research devoted to the investigation of branding genesis. The study is focused on the cylinder seals that have been used in the economic life during the very beginning of the Egyptian state. The time scope of the study encompasses Dynasties I-III. The thorough investigation of the cylinder seals includes defining their typology on the basis of the text context engraved on them. A comparative analysis of the ancient (proto)brands versus the contemporary analogues is presented. As the research includes hundreds of seals classified in major classes, classes, cluster groups and clusters the total volume of the analysis is huge – because of that the results will be published consecutively in several publications.